COMPARATIVE INVESTIGATION ON FIBER DIMENSIONS OF TRUNK AND BRANCH WOOD OF CARPINUS BETULUS L. - Saeed Mahdavi; masoudreza habibi (تحقیقات علوم چوب و کاغذ ایران, 2004)
Growing interest in wood and paper consumption in Iranian industries and forest utilization constraints call for alternative approaches on the exploitation trend. Lately, industrial countries consider utilization of small diameter trees and branches residual wood. European hornbeam with vast coverage among the other species in Iran can be an alternative to tree shortage of raw material for the sector. This study showed that the branch fiber dimensions have significantly differed compare to trunk.Average fiber length was measured as 1.76mm for breast height of three trunks and 1.43 mm for two branches samples. Fiber length increased from crown downward to the stump and also from pith to bark, but there was a significant negative correlation between the variations and tree height. Fiber length increased in trees of up to 30 years of age and decreased afterwards. There is no orderly pattern from tree base to the upper branches.Runkel and flexibility coefficients of branch were better than trunk despite of higher fiber dimensions in trunk.